2012
DOI: 10.3109/13685538.2012.669437
|View full text |Cite
|
Sign up to set email alerts
|

Associations of the lower urinary tract symptoms with the lifestyle, prostate volume, and metabolic syndrome in the elderly males

Abstract: This study aimed to evaluate the influence of the lifestyle, prostate volume (PV), and metabolic syndrome (MS) on lower urinary tract symptoms (LUTS) in the elderly males. A total of 764 men aged greater than 40 years were enrolled. Their severities of LUTS were assessed by the International Prostate Symptom Score questionnaire, while their MS was diagnosed according to the criteria developed by the National Cholesterol Education Program Adult Treatment Panel III. Lifestyle factors, PV, and components of MS we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
1
9
0
1
Order By: Relevance
“…Conversely, in our study, although prostate volume was significantly greater in BPH patients with MetS than in those without, MetS was only related to a longer duration of LUTS, but not associated with maximum urinary flow rate (one of the factors used to estimate the urethral obstruction grade and detrusor contractility grade in men with LUTS) or IPSS value. Several studies [32,33] investigating the male population in China reported that the presence of any components of MetS was not related to LUTS as assessed by the IPSS, which was similar to our result. LUTS, in addition to causing physical obstruction from prostatic hyperplasia, can be influenced by multiple factors, such as vascular, neurological, muscular abnormalities of the bladder, altered bladder neck compliance and tone, prostate and pelvic floor, aging and lifestyle factors, in a complex interplay [34,35].…”
Section: Discussionsupporting
confidence: 82%
“…Conversely, in our study, although prostate volume was significantly greater in BPH patients with MetS than in those without, MetS was only related to a longer duration of LUTS, but not associated with maximum urinary flow rate (one of the factors used to estimate the urethral obstruction grade and detrusor contractility grade in men with LUTS) or IPSS value. Several studies [32,33] investigating the male population in China reported that the presence of any components of MetS was not related to LUTS as assessed by the IPSS, which was similar to our result. LUTS, in addition to causing physical obstruction from prostatic hyperplasia, can be influenced by multiple factors, such as vascular, neurological, muscular abnormalities of the bladder, altered bladder neck compliance and tone, prostate and pelvic floor, aging and lifestyle factors, in a complex interplay [34,35].…”
Section: Discussionsupporting
confidence: 82%
“…Although a pathophysiological link between components of Met S and LUTS has been proposed [162163], our understanding of the complex interaction between these elements is limited. While a host of studies point to a link between Met S and LUTS (Table 2), other studies have suggested that no relationship exists between Met S and LUTS [164165166]. Thus, large, prospective studies are needed to ascertain such relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has found a relationship between LUTS/BPH and MetS [9,10,11]. However, the severity of LUTS is only one aspect of the clinical progression of BPH.…”
Section: Discussionmentioning
confidence: 99%